Unusual presentations of eosinophilic gastroenteritis: Two case reports - Leal, Regina; Fayad, Leonardo; Vieira, Daniella; Figueiredo, Teresa; Lopes, Aldemar; Carvalho, Roberta; Dantas-Corrêa, Esther; Schiavon, Leonardo; Narciso-Schiavon, Janaína (Turkish Journal of Gastroenterology, 2014)
Abstract Eosinophilic gastroenteritis is a rare disease that is characterized by eosinophil infiltration in one or multiple segments of the gastrointestinal tract. The etiology of this condition remains unknown. Eosinophilic gastroenteritis has heterogeneous clinical manifestations that depend upon the location and depth of infiltration in the gastrointestinal tract, and eosinophilia may or may not be present. This article reports two cases of eosinophilic gastroenteritis. The first is that of a 49-year-old woman with abdominal pain, ascites, eosinophilia, and a history of asthma. The second case is that of a 69-year-old male with a history of loss of appetite, belching, postprandial fullness, heartburn, and a 5-kilogram weight loss over a period of 9 months; ultimately, the patient was diagnosed with a gastric outlet obstruction due to pyloric stenosis. The rare character of eosinophilic gastroenteritis and its varied clinical presentations often lead to delayed diagnoses and complications. Case reports may help to disseminate knowledge about the disease, thereby increasing the likelihood of early diagnosis and intervention to prevent complications.